Стандарт доказування «поза розумним сумнівом» у кримінальному провадженні - Степаненко, Андрій Сергійович; Степаненко, Андрей Сергеевич; Stepanenko, Andriy S. (My University, 2017)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.09 - кримінальний процес та криміналістика; судова експертиза; оперативно-розшукова діяльність. - Національний університет «Одеська юридична академія», Одеса, 2016. Дисертація є першим у вітчизняній науці спеціальним комплексним дослідженням стандарту доказування «поза розумним сумнівом» у кримінальному провадженні на основі міжнародного та європейського досвіду в умовах дії КПК України 2012 р. У дисертації з'ясовано основні вектори розвитку стандарту доказування «поза розумним сумнівом», визначено поняття стандарту доказування «поза розумним сумнівом», його місце в системі стандартів доказування, а також мету доказування з позиції стандарту доказування «поза розумним сумнівом». Проаналізовано практику застосування та визначення стандарту доказування «поза розумним сумнівом» на національному (Австралія, Грузія, Канада, КНР, Нова Зеландія, РФ, СК, США, ФР, ФРН) та міжнародному (ЄСПЛ, МКС, МТКЮ, МТР) рівнях. Окрему увагу приділено перспективам застосування стандарту доказування «поза розумним сумнівом» у вітчизняному кримінальному процесуальному законодавстві та доктрині, де було розглянуто співвідношення стандарту доказування «поза розумним сумнівом» з внутрішнім переконанням, вирішенням цивільного позову та міжгалузевою преюдицією. Сформульовано науково-обґрунтовані пропозиції щодо внесення змін та доповнень до КПК України щодо дії стандарту доказування «поза розумним сумнівом» у кримінальному провадженні.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.09 - уголовный процесс и криминалистика; судебная экспертиза; оперативно-розыскная деятельность. - Национальный университет «Одесская юридическая академия», Одесса, 2016. Диссертация является первым в отечественной науке специальным комплексным исследованием стандарта доказывания «вне разумного сомнения» в уголовном производстве на основе международного и европейского опыта в условиях действия УПК Украины 2012 г. В диссертации определены основные векторы развития стандарта доказывания «вне разумного сомнения», определено понятие стандарта доказывания «вне разумного сомнения», его место в системе стандартов доказывания, а также цель доказывания с позиции стандарта доказывания «вне разумного сомнения». Проанализирована практика применения и определения стандарта доказывания «вне разумного сомнения» на национальном (Австралия, Грузия, Канада, КНР, Новая Зеландия, РФ, СК, США, ФР, ФРГ) и международном (ЕСПЧ, МУС, МТБЮ, МТР) уровнях. Отдельное внимание уделено перспективам применения стандарта доказывания «вне разумного сомнения» в отечественном уголовном процессуальном законодательстве и доктрине, где было рассмотрено соотношение стандарта доказывания «вне разумного сомнения» с внутренним убеждением, разрешением гражданского иска и межотраслевой преюдиции. Сформулированы научно-обоснованные предложения о внесении изменений и дополнений в УПК Украины относительно действия стандарта доказывания «вне разумного сомнения» в уголовном производстве.

Thesis for obtaining scientific degree of Candidate of Juridical Science, specialty 12.00.09 - criminal procedure and forensic science; forensic enquiry and operational-search activity. - National University "Odessa Law Academy", Odessa, 2016. The thesis is the first comprehensive research in domestic science on the standard of proof "beyond a reasonable doubt" in criminal proceedings based on international and European experience under the action of Criminal Procedural Code of Ukraine 2012. The main theoretical issues of "beyond a reasonable doubt" standard are examined. It is argued that phrase "beyond a reasonable doubt" is a part of more complex concept - standard of proof. "Beyond a reasonable doubt" standard is a criminal standard of proof and has the following features: 1) variability of standard of proof, which is dependent upon the field of application and subject; 2) strong relation between standard and burden of proof; 3) it is a decision threshold for the subject of decision making which sets an evidential level (measure) for a fact to be considered as existent. It is stated that from "beyond a reasonable doubt" standard standpoint, credibility as the highest level of probability is the only purpose of proving. It is also justified that philosophical category of "truth" is not applicable in the area of criminal process as purpose of proving due to the vagueness of the term and the limitations and constraints of proving in criminal procedure. On the basis of analysis of key influential works main historical vectors of development and interpretation of "beyond a reasonable doubt" standard were unfolded: 1) rational (as a mean to overcome uncertainty) and 2) theological (as a mean to overcome "burden of sentencing"). It is justified that the standard of proof "beyond a reasonable doubt" doesn't conflict with the concept of "inner conviction," but makes its psychological aspects more formal by answering the question on sufficiency of present evidence in order to make a criminal procedural decision. It is asserted that all criminal procedural court decisions are probabilistic in nature and thus inevitableness of judicial errors. These judicial errors may be distributed by setting "beyond a reasonable doubt" standard. It is possible to argue that society (state) put greater weight to Type I errors (false convictions) than to Type II errors (false acquittals). Analysis of current criminal procedural legislation of Ukraine, and the practices of the European Court of Human Rights, permits the argument that leaving a civil action undecided by a criminal court, and thus giving an opportunity for civil claimant to file the same civil claim before another civil court, fits with the concept of standard of proof. Standard of proof "beyond a reasonable doubt" could only be used in criminal proceedings to answer the ultimate question - whether the defendant is guilty or not. Though civil action is triggered because of criminal misconduct, the acquittal of the defendant is made on a criminal standard which is not applicable in civil trial and which is far higher than civil standard. Accordingly, the civil claimant has a right for compensation, as well as a right to file the same civil claim to the civil trial. Such a procedure is consistent with the practice of the European Court of Human Rights, and does not violate the presumption of innocence enshrined in the Article 6 of the European Convention on Human Rights. Theoretically justified proposals and changes to the Criminal Procedural Code of Ukraine in the sphere of enforcement of standard of proof "beyond a reasonable doubt" in criminal proceedings are formulated.
дис. ... к.ю.н.: 12.00.09
Степаненко А.С. Стандарт доказування «поза розумним сумнівом» у кримінальному провадженні: дис. ... канд. юрид. наук: 12.00.09 / Степаненко Андрій Сергійович. - Одесса, 2017. - 234 с.
Keywords: доказування; мета доказування; істина; стандарт доказування; стандарт доказування «поза розумним сумнівом»; внутрішнє переконання; міжгалузева преюдиція; доказывание; цель доказывания; истина; стандарт доказывания; стандарт доказывания «вне разумного сомнения»; внутреннее убеждение; межотраслевая преюдиция; proving; purpose of proving; truth; standard of proof; standard of proof "beyond a reasonable doubt"; inner conviction; interbranch prejudice